An evaluation system for electronic retrospective analyses in radiation oncology - Implemented exemplarily for pancreatic cancer - Kessel, Kerstin A.; Jaeger, Andreas; Bohn, Christian; Habermehl, Daniel; Zhang, Lanlan; Engelmann, Uwe; Bougatf, Nina; Bendl, Rolf; Debus, Juergen; Combs, Stephanie E. (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2013)
To date, conducting retrospective clinical analyses is rather difficult and time consuming. Especially in radiation oncology, handling voluminous datasets from various information systems and different documentation styles efficiently is crucial for patient care and research. With the example of patients with pancreatic cancer treated with radio-chemotherapy, we performed a therapy evaluation by using analysis tools connected with a documentation system. A total number of 783 patients have been documented into a professional, web-based documentation system. Information about radiation therapy, diagnostic images and dose distributions have been imported. For patients with disease progression after neoadjuvant chemoradiation, we designed and established an analysis workflow. After automatic registration of the radiation plans with the follow-up images, the recurrence volumes are segmented manually. Based on these volumes the DVH (dose-volume histogram) statistic is calculated, followed by the determination of the dose applied to the region of recurrence. All results are stored in the database and included in statistical calculations. The main goal of using an automatic evaluation system is to reduce time and effort conducting clinical analyses, especially with large patient groups. We showed a first approach and use of some existing tools, however manual interaction is still necessary. Further steps need to be taken to enhance automation. Already, it has become apparent that the benefits of digital data management and analysis lie in the central storage of data and reusability of the results. Therefore, we intend to adapt the evaluation system to other types of tumors in radiation oncology. © 2013 SPIE.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Documentation system; Electronic analysis; Evaluation; Pancreatic cancer; Retrospective